Different LED light intensity and quality change perennial ryegrass (Lolium perenne L.) physiological and growth responses and water and energy consumption - Brito, Cátia; Ferreira, Helena; Dinis, Lia-Tânia; Trindade, Henrique; Marques, David; Correia, Carlos Manuel; Moutinho-Pereira, José (Frontiers in Plant Science, 2023)
Light intensity and spectral composition highly affects plant physiology, growth and development. According to the growing conditions, each species and/or cultivar have an optimum of light intensity to drive photosynthesis, and different light colors trigger photosynthetic responses and regulate plant development differently. For the maintenance of natural sports pitches, namely for professional football competitions, the turf quality is a key condition. Due to the architecture of most football stadiums, the lawns receive low intensity of natural light and supplementary artificial lighting is required. The use of light-emitting diodes (LEDs) can have a high cost-benefit than the traditional high-pressure sodium lamps. The continuous emission spectrum, combined with high spectral selectivity and adjustable optical power can be used to optimize plant growth and development. Thus, perennial ryegrass (Lolium perenne L.) plants, commonly used for lawns, were primarily grown under three different light intensities (200, 300, 400 μmol m−2 s−1) of cool white light. Despite the higher water and energy consumption, 400 μmol m−2 s−1 maximizes the plants efficiency, with higher photosynthetic rates and foliar pigments concentration and more foliar soluble sugars and aboveground biomass accumulation. Then, it was evaluated the perennial ryegrass (Double and Capri cultivars) response to different spectral compositions [100% cool white (W), 80% Red:20% Blue (R80:B20), 90% Red:10% Blue (R90:B10) and 65% Red:15% Green:20% Blue (R65:G15:B20)] at 400 μmol m−2 s−1. Both cultivars exhibited similar responses to light treatments. In general, W contributed to a better photosynthetic performance and R90:B10 to the worst one. Water consumption and aboveground biomass were equal in all the light treatments. R80:B20 allow energy savings of 24.3% in relation to the W treatment, showing a good compromise between physiological performance and energy consumption.